Design, fabrication and evaluation of microemulsion based gel of essential oil of thymus vulgaris for superficial fungal infections (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Although fungus being part of the commensal skin micro-structuring, various pathogenic commensals colonizes on human skin leading to superficial fungal infections. Owing to the resistance of present therapeutic treatments available, microbial resistance and serious hypoallergic reactions have been a concern to explore the phyto-therapeutic nutrients for treatment of fungal infections. One such plant essential oil-based formulation is thyme oil derived from the leaves of thymus vulgaris. The aim of present work i.e. development of thyme oil based microemulsion for treatment of fungal infections due to candida and trichophyton species. The thyme oil loaded microemulsion based gel was constructed using D-optimal design and the optimized final formulation contains 0.82% of oil, 9.22% of Smix and 89.95% of water. The optimized microemulsions was pale yellow to amber transparent microemulsion with globule size of 14.23 ± 0.3 nm, zeta potential of -0.69 mV and PDI value 0.00143 indicating a stable microemulsion. The microemulsion based gel formed had a pH of 6.03, appreciable viscosity and rheological properties. The drug release of formulation was 100.0 ± 0.22%. The % of drug permeated in skin layers was found to be 15.53 ± 0.22%. While % drug retention on the skin surface was found to be 26.32 ± 0.26% and within skin layers was found to be 58.47 ± 0.22%. The microemulsion based MBG was found to be safe on the dermis and efficacious then the marketed product and hence, promises its utilization as a safe and efficacious formulation for treatment of dermal infections.